(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Traffic congestion is a major problem in cities of developing Countries like India. Growth in urban population and the middle-class segment contribute significantly to the rising number of vehicles in the cities. Congestion on roads eventually results in slow moving traffic, which increases the time of travel, thus stands-out as one of the major issues in metropolitan cities. This paper presents an intelligent traffic control system to pass emergency vehicles smoothly. Each individual vehicle is equipped with special radio frequency device. We use radio frequency (Rf)transmitter (Tx) and receiver (Rx) modules at ambulance and traffic signal respectively. It monitors vehicles that passes on a path during a specified duration. It also determines the network congestion, and hence the green light duration for that path. If the ambulance passes through the path it switches on the green light until it passes the signal area.